Analisis Pengaruh Pembiayaan Mudharabah dan pembiayaan Musyarakah Terhadap Profitabilitas Bank umum Syariah di Indonesia periode 2016 – 2020 - Amara Elprida Sani (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
The purpose of this research is to knowing the effect of mudharabah financing and musyarakah on the profitability which will use the ROA Ratio (Return on Assets). The type of research used during the research is descriptive quantitative. The samples used in this study is 6 Islamic banks and the data used are external secondary data and literature study in the form of annual financial reports consisting of PT Bank BNI Syariah, PT Bank BRI Syariah, PT Bank Syariah Mandiri, PT Bank BCA Syariah, PT Bank Muamalat Indonesia and PT Bank Bukopin Syariah for 5 years from the period 2016 to 2020. from the result of the research that has been done, there is influence of X1 or the mudharabah variable and X2 or the musyarakah variable on Y or the profitability variable significantly.Keyword: Mudharabah,Musyarakah,ROA